Why Geography? A study of post-16 choices in a sixth form college - Cohen-Lask, Noami (2017)
Geography as a school subject has had something of a contested history as it has developed as a discipline. Recent developments such as its inclusion as an EBACC option, and designation as a ‘facilitating subject’ have served to increase its popularity as an A Level subject. It is marketed as an instrumentally useful subject which can provide transferrable skills in an increasingly competitive labour market. This shift has come at a time of change for the subject and curriculum more generally in the wake of the 2010 White Paper. This so-called knowledge turn has sought to re-centre the curriculum around core subject knowledge. This change in policy has been the source of much debate, but students are rarely invited to participate. The aim of this dissertation is to better understand how student perspectives of A Level geography fit within this wider discussion. In order to understand how students’ perceptions of geography relate to these debates, this dissertation will research the opinions of the students within my current teaching context: a large sixth form college in West Sussex. The research uses an online questionnaire distributed to all 190 A Level geography students at the college, followed by in depth focus groups. Analysis of the results suggest that many students choose geography largely due to an interest in the content, due to the subject’s ability to explain everyday experiences and also take students beyond their existing knowledge. On the other hand, not all students are clear on the nature of geographical knowledge and base their perceptions of the subject on more superficial concerns. This suggests that for teachers, there is still work to be done as curriculum makers to emphasise the unique and powerful nature of powerful geographical knowledge.